On the Stiffness and Damping Coefficients of Constant Flow Valve Compensated Conical Hydrostatic Journal Bearing with Micropolar Lubricant. (2016) - Rana, N.K.; Gautam, S.S.; Verma, Suresh; Rahmani, F.
Abstract: A theoretical analysis for performance characteristics of a conical multirecess hydrostatic journal bearing compensated with constant flow valve has been carried out considering micropolar lubricant. The numerical solution of the modified Reynolds equation for the conical bearing has been done using finite element method with necessary boundary conditions. The performance characteristics have been presented for various values of the restrictor design parameter, load, micropolar parameters, semi-cone angle and aspect ratio (L/D ratio) of the bearing at zero speed. It has been observed that the bearing develops large stiffness and damping coefficients with increase in restrictor design parameter, micropolar effect and semi-cone angle.